2004
DOI: 10.1007/s00467-003-1283-1
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone levels in pubertal uremic adolescents treated with growth hormone

Abstract: We have previously described severe hyperparathyroidism during the pubertal growth spurt in three uremic adolescents treated with recombinant human growth hormone (rhGH). Here we investigate the possible role of puberty in the genesis of hyperparathyroidism during rhGH treatment of a large cohort of patients. Data from 67 uremic patients treated with rhGH from five Italian pediatric nephrology centers were retrospectively recorded every 3 months starting 1 year before rhGH administration. The mean (+/-SD) rhGH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Increased serum PTH levels after rhGH therapy has previously been reported, especially in fast-growing pubertal uremic patients [21][22][23]. Likewise, the first 2 years of life are characterized by high growth velocity, suggesting that similar mechanisms apply also to infants with CRF.…”
Section: Discussionmentioning
confidence: 89%
“…Increased serum PTH levels after rhGH therapy has previously been reported, especially in fast-growing pubertal uremic patients [21][22][23]. Likewise, the first 2 years of life are characterized by high growth velocity, suggesting that similar mechanisms apply also to infants with CRF.…”
Section: Discussionmentioning
confidence: 89%
“…However, in a recent prospective study, no increased frequency of epiphyseal slipping associated with the use of growth hormone was reported [78]. After the start of GH administration, an increase of PTH levels was observed [79, 80]. …”
Section: Recommendationsmentioning
confidence: 99%
“…CaSR are also expressed in the kidney tubules and will sense a fall in serum Ca, resulting in an increase in Ca reabsorption. These positive feedback mechanisms act to increase serum Ca levels PTH levels, while Picca et al [15] demonstrated that PTH levels tended to rise in pubertal CKD patients treated with rhGH, although growth was not adversely affected.…”
Section: Growth and Pth Through The Phasesmentioning
confidence: 99%